Mycorrhizal synthesis between the truffle Terfezia claveryi and Some Annual dicot plants using different culture media - Al-jaff, Bahrouz Mahmood Amin; Amin, Miqdad Hamasalh Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2018)
The desert truffles were collected from the local wild and the other purchased from local markets. Only two truffle species were identified, Terfezia claveryi and Terfezia boudieri. The wild host plants Helianthemum salicifolium, Heliotropium lasiocarpum, Polygonum aviculare and Amaranthus blitoides and the farm Apium graveolens were chosen and identified according to the identification schemes used for synthesizing mycorrhiza with T. claveryi on M.S. medium, M.S. medium supplemented semisolid PDA and sodium deoxycholate supplemented medium. The mycelial suspension was prepared from the glebal matrix and plated on M.S. medium supplemented Potato dextrose agar (PDA), while seeds of the host plants were germinated on Murashige and Sckoog medium (M.S.). Regarding the mean percent of synthesis of internal and external mycorrhizal associations there were significant differences among the five host plants (P value = 0.000), while no differences seen among the three culture media (P value = 0.851). There were also significant differences among the mean percents of interaction plants and the media (P value = 0.000), and among the periods of time required for mycorrhization between T. claveryi and the host plants using the three culture media, M.S. Medium: external (p = 0.002) internal (p = 0.001), M.S. medium supplemented semisolid PDA: external (p = 0.007) internal (p = 0.001), sodium deoxycholate supplemented medium: internal (p = 0.000), while there was no significant difference between the period of time with respect to external structure when sodium deoxycholate supplemented medium was used (p = 0.033). It was concluded that T. claveryi synthesized better internal and external mycorrhizal association with the two hosts Polygonum aviculare and Helianthemum salicifolium by using any of the three media. An additive advantage of these two hosts is that they showed adequate germination rates (73.3% and 66.6% respectively) within shorter mean germination times (2.343 and 2.390 days respectively).
Keywords: Truffle; Terfezia claveryi; mycorrhiza